KEBIASAAN SARAPAN BERHUBUNGAN DENGAN KONSENTRASI BELAJAR PADA SISWA SDN SUKOHARJO I MALANG - Lydia Verdiana; Lailatul Muniroh (Universitas Airlangga, 2017)
Many school-aged children skip breakfast whereas breakfast is useful for improving learning concentration which leads to the improvement of their learning achievement. This study was aimed to analyze correlation between the types of breakfast with the concentration level during the learning process among students at SDN Sukoharjo I Malang. The study was conducted using cross sectional design with an analytic observational approach. The interview was conducted to 43 students of grade 5 who were randomly selected by using simple random sampling technique. Interview using 2x24 hours food recall questionaire was done to obtain the type of breakfast habit. Data on concentration level was obtained by using Clerical Speed and Accuracy Test instrument. Spearman Correlation was performed to test correlation between type of breakfast habit and concentration level. The result showed that one third respondents are having regular breakfast (37.2%). These children were also discovered to have inadequate levels of energy, carbohydrate, protein and fat. As much as 23,3% students have good concentration levels and excellent concentration levels (46.5%), although there are still some students have low levels of concentration. There was signifi cant correlation between breakfast and the level of concentration (p = 0.001). Proportion of students who have good concentration level was higher among students who have healthy breakfast compared to among those who do not have regular breakfast and no breakfast. The students’ awareness about the importance of breakfast needs to be improved through physical education by the teacher.